Acceptability of HPV Vaccination in Young Students by Exploring Health Belief Model and Health Literacy - Alessandra Fallucca; Palmira Immordino; Luca Riggio; Alessandra Casuccio; Francesco Vitale; Vincenzo Restivo (Vaccines, 2022)
Evidence on the human papillomavirus (HPV) vaccine shows that it is effective in reducing the burden of HPV-related diseases. For more than 15 years the HPV vaccine has been offered free of charge in Italy to girls from the age of 12. Over time, the free offer of the HPV vaccine has also been extended to boys and to young adults at risk of developing HPV lesions. Despite the HPV vaccine’s effectiveness and availability, vaccination coverage is low in Italy, with a reported value of 46.5% in 2020. Furthermore, in the southern administrative regions, vaccination coverage is even lower than national values, with 25.9% coverage in Sicily. A cross-sectional study was conducted among university and high school students in the Palermo area (Sicily, Italy) in order to identify the determinants of HPV vaccination adherence by using a questionnaire that investigated factors of HPV vaccine practice. The study explored the behavioral attitude by using the Health Belief Model (HBM), and also used the SILS test and the METER test to investigate the level of health literacy (HL). Overall, 3,073 students were enrolled, and less than a third reported they had completed the vaccination schedule (n = 925, 30.1%). Multivariable analysis showed that the factors directly associated with the adherence to HPV vaccination were female sex (OR = 4.43, p < 0.001), high HBM total score (OR = 4.23, p < 0.001), good HL level (OR = 1.26, p = 0.047), parents (OR = 1.78, p = 0.004), general practitioner (OR = 1.88, p = 0.001), and educational material provided by public vaccination services (OR = 1.97, p = 0.001) as HPV vaccine information sources. Further health-promotion programs focused on improving HL and perception of the HPV vaccine’s benefits should be implemented in order to achieve the desirable 95% vaccination coverage.